The role of Airbnb creating a “new”-old city centre: facts, problems and controversies in Porto - Pedro Chamusca; José Rio Fernandes; Luís Carvalho; Thiago Mendes (Boletín de la Asociación de Geógrafos Españoles)
Urban tourism growth, favoured by short term rental platforms like Airbnb, is changing the cities dramatically. All over Europe local governments have been facing unbridled growth of the so-called sharing economy and developed different regulatory approaches: full prohibition; laissez-faire; and different sorts of limitations. We take Porto as a case-study, considering the exponential growth of tourism, Airbnb and floating city users over the past decade. We make use of qualitative and quantitative methods and draw on the official AirDNA database to analyse the relation between Airbnb and urban transformation, and the governance context. We conclude that the growth of floating city-users –stimulated by Airbnb– has been the main driver of urban change. The case of Porto –which in many ways illustrates the fast growth of short-term, rental-driven urban tourism in southern Europe– demonstrates that Airbnb’s global corporate narrative around property sharing, micro-entrepreneurship and tourism democratization hardly fits the urban reality of host professionalization, income concentration and growing massification. In this context, besides laissez-faire, urban sustainability concerns call for smarter regulatory approaches associated with more widely shared visions, and clear short, medium and long-term objectives.